PERAN PENGENDALIAN ANGGARAN KETAT DAN ETIKA MEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Adnyana Putra, Putu; Rasmini, Ni Ketut; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018DO - 10.24843/EEB.2018.v07.i01.p01, 2018)
This study to examine that tight budget control and ethics climate as a moderation variabels  influence the partisipative budgeting on budgetary slack. The research was conducted at 39 SKPD in Tabanan regency. The Sample was taken by disproportionate stratified random sampling. Data collected by survey with distributing questionnaires. The respondents as many as 273 officials from echelon II, III and IV. The regression analysis shows that the moderation of tight budgetary control were able to weaken the effect of budgetary participation on budgetary slack. Ethics able to weaken the effect of budgetary participation on budgetary slack.
Keywords: Participative Budgeting, Tight Budget Control, Ethics, Budgetary Slack